NAMPT-mediated NAD+ biosynthesis is indispensable for adipose tissue plasticity and development of obesity - Karen Nørgaard Nielsen; Julia Peics; Tao Ma; Iuliia Karavaeva; Morten Dall; Sabina Chubanava; Astrid L. Basse; Oksana Dmytriyeva; Jonas T. Treebak; Zachary Gerhart-Hines (Elsevier, 2018)
Objective: The ability of adipose tissue to expand and contract in response to fluctuations in nutrient availability is essential for the maintenance of whole-body metabolic homeostasis. Given the nutrient scarcity that mammals faced for millions of years, programs involved in this adipose plasticity were likely evolved to be highly efficient in promoting lipid storage. Ironically, this previously advantageous feature may now represent a metabolic liability given the caloric excess of modern society. We speculate that nicotinamide adenine dinucleotide (NAD+) biosynthesis exemplifies this concept. Indeed NAD+/NADH metabolism in fat tissue has been previously linked with obesity, yet whether it plays a causal role in diet-induced adiposity is unknown. Here we investigated how the NAD+ biosynthetic enzyme nicotinamide phosphoribosyltransferase (NAMPT) supports adipose plasticity and the pathological progression to obesity. Methods: We utilized a newly generated Nampt loss-of-function model to investigate the tissue-specific and systemic metabolic consequences of adipose NAD+ deficiency. Energy expenditure, glycemic control, tissue structure, and gene expression were assessed in the contexts of a high dietary fat burden as well as the transition back to normal chow diet. Results: Fat-specific Nampt knockout (FANKO) mice were completely resistant to high fat diet (HFD)-induced obesity. This was driven in part by reduced food intake. Furthermore, HFD-fed FANKO mice were unable to undergo healthy expansion of adipose tissue mass, and adipose depots were rendered fibrotic with markedly reduced mitochondrial respiratory capacity. Yet, surprisingly, HFD-fed FANKO mice exhibited improved glucose tolerance compared to control littermates. Removing the HFD burden largely reversed adipose fibrosis and dysfunction in FANKO animals whereas the improved glucose tolerance persisted. Conclusions: These findings indicate that adipose NAMPT plays an essential role in handling dietary lipid to modulate fat tissue plasticity, food intake, and systemic glucose homeostasis. Keywords: Adipose metabolism, Obesity, NAMPT, NAD+ synthesis, Energy homeostasis, Adipose plasticity, Glucose homeostasis